Community School Implementation in Rural Vermont - Knox, Peter N.; Garnett, Bernice; DeCarolis, Jess; Haensch, Johannes (Educational policy (Los Altos, Calif.), 2025)
This study highlights the Community Schools (CS) implementation experience of five rural Vermont schools. Principals and CS coordinators participating in a state-funded program aimed at CS establishment were interviewed to understand better their experience with implementing a school/district-wide policy and reform effort. Findings suggest several elements play a critical role in the successful implementation of rural CSs, including leveraging already-present community engagement practices, school leader embodiment of CS values/mentality, as well as collaborative leadership practices that broaden participation and level the field for all parties involved. Implications for community school implementation within rural contexts are discussed.